The role of curriculum design and teaching materials in pronunciation learning - Alghazo, Sharif (Research in Language, 2015)
This paper aims to provide insights into the role of curriculum design and teaching materials in the development of English pronunciation skills in EFL contexts. One of the main contextual factors negatively affecting the development of pronunciation abilities of EFL learners relates to the ‘often-unchanging’ curriculum design and the ‘blind’ choice of teaching materials without regard to students’ needs and goals. This study utilises structured interviews and focus group discussions (N=2 sessions) to elicit the views of a group (N=71) of third- and fourth-year English-major students at a university college in Saudi Arabia on the appropriateness of the curriculum design and teaching materials to their learning expectations in the area of English pronunciation. The results show that the great majority of students spoke unfavourably about the overall curriculum and teaching materials and considered those to be among the obstacles that they encounter in their learning of English pronunciation. This finding raises the question of curriculum design of English language teaching programs and the extent to which these curricula meet the needs of learners. The study suggests that a reformation of the structure of the curriculum in the study context is urgently needed and that more involvement of students’ perspectives on the design of curricula is of major importance.